MANAJEMEN MEDIA INFORMASI DALAM BIROKRASI: STRATEGI PENINGKATAN KUALITAS KONTEN SOSIAL MEDIA INSTAGRAM SEBAGAI PUBLIKASI LAYANAN ADMINISTRASI KECAMATAN KREMBUNG SIDOARJO - Rifka Firzanah Rahmasari; Moh. Dey Prayogo; Alvira Febrian Pristiana (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Information media management in an institution is quite important. Especially in Instagram social media. In Krembung Sub-district Institution, information is conveyed through social media. By paying attention to the elements in the features of the smart application. Paying attention to the elements of beauty and neatness is one of the attractions for the audience to visit the social media account page. Content that is well presented and neat makes the audience interested. The bureaucratic flow of the Institution is often shared on social media accounts. The community can easily access the information they want to get or obtain. Communication carried out through the media is quite effective in getting feedback. All features in the application are the key to successful media management by paying attention to all aspects of it.